Kreishohlprofil-X-Knoten aus nichtrostenden Stählen unter Axialbeanspruchung - Lipp, Andreas (Berichte zum Stahl- und Leichtbau / Karlsruher Institut für Technologie, Versuchsanstalt für Stahl, Holz und Steine, Stahl- und Leichtbau, 2016)
At present, the design of unstiffened, welded circular hollow section (CHS) joints made of stainless steels is insufficiently regulated since all available design rules are based upon results of investigations on CHS joints made of unalloyed and low-alloy structural steels. This work deals with the load-bearing capacity of uniplanar CHS X-joints made of stainless steels under predominantly static axial loading. A design concept for these type of joints was developed.